Analisis Nilai Moral Ada Buku Cerita Bawang Putih Bawang Merah - Maulidia, Andini; Nabila, Puan Herliya; Arifin, Ach. Faizul; Masodi, Masodi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The story of Bawang Merah Bawang Putih is one of the popular fables in Indonesia that contains various moral values that can be applied in the formation of children's character. This study aims to analyze the moral values in the story and its application in character education in the modern era. The method used is descriptive qualitative with a content analysis approach to various versions of the story documented in books and digital publications. The results of the study show that this story contains the main moral values, such as honesty, hard work, patience, and justice. Bawang Putih's honesty and sincerity lead to happiness, while Bawang Merah's lies and laziness lead to punishment, illustrating that every action has consequences. Furthermore, this story also teaches the importance of perseverance and patience in facing difficulties and instills the concept of justice in life. Thus, the Bawang Merah Bawang Putih fairy tale remains relevant as a medium for character learning for the younger generation and can be used as a source of moral education in the midst of modern progress.